Oriental Mothers, Occidental Daughters, and the Eternal Ties that Bind - Tapales, Proserpina Domingo (Review of Women's Studies; Vol 1 No 2 (1991): Review of Women's Studies Volume I, Number 2 (1990-1991))
Book review of The Joy Luck Club by Amy Tan. New York: Ballantine Books, 1989.